A Role for Dogs in Advancing Cancer Immunotherapy Research - Dow, Steven (Frontiers in Immunology, 2020)
The field of immuno-oncology has advanced so rapidly that there is large need for additional new animal models with which to effectively and efficiently evaluate cancer immunotherapies, particularly immunotherapy combinations with conventional therapeutics, including targeted agents, chemotherapy, and radiation therapy. While current rodent cancer models are essential for early proof-of-concept and mechanistic studies for immune therapies, these models have limitations with regards to predicting the ultimate effectiveness of new immunotherapies in humans. The value of the dog cancer model was recently recognized by the National Institute of Medicine. Therefore, this review is intended to summarize key aspects of the dog cancer model that make the model particularly well-suited to evaluating new cancer immunotherapies and drug combinations. The review will focus on areas of investigation and cancer types in which the dog model currently is most likely to impact clinical immuno-oncology research and new drug development. Immune reagent availability is discussed, along with some unique challenges associated with the dog immunotherapy model. The intent of this review is to increase awareness of the dog cancer model and stimulate additional studies that may benefit both man and man’s best friend.